Implementation of Project-Based Learning: Utilizing Natural Rocks as Waste Absorbents - Oktaffi Arinna Manasikana; Nur Hayati; Noer Af'idah; Mulia Rasyidi (Universitas Pendidikan Mandalika, 2023)
The current study explores the advantages of project-based learning, which involves using real-world problems as a basis for gathering and integrating new knowledge. Specifically, the study investigates the implementation of project-based learning in the Solid Interface course within the Natural Science Education program. Through direct practice, students are required to master the course material, making it more applicable to real-world situations. To assess the effectiveness of this approach, an experimental method was used, which involved students conducting experiments, observing and experiencing the process, and presenting their results to the class for evaluation. This method provides students with the opportunity to learn independently, follow a process, analyze objects, draw evidence, and draw their own conclusions from the process being carried out. The objective of this research is to apply the project-based learning model and explore the utilization of natural zeolite rocks as an absorbent for heavy metal ions, specifically Plumbum and cadmium waste. The study successfully implemented the project-based learning approach, and the stages were carried out successfully. The results showed that cadmium is a silvery white metal that can be forged, and exposure to this metal can cause paralysis and even death. The study investigated the adsorption of metal ions by chelate Zeolite-EDTA on variations of particle size, including 212 μm, 125 μm, and 90 μm, with an adsorbate/adsorbent ratio of 20 mL/g, 30 mL/g, 40 mL/g, and 50 mL/g. The results indicated that the best adsorption of lead waste occurred with Zeolite-EDTA chelate at a particle size of 212 μm, with an adsorbate/adsorbent ratio of 30 mL/g. For cadmium wastewater, the best adsorption was achieved with Zeolite-EDTA chelate at a particle size of 212 μm, with an adsorbate/adsorbent ratio of 20 mL/g. These findings contribute to the growing body of literature on project-based learning and the use of natural zeolite rocks as an absorbent for heavy metal ions.